2004
DOI: 10.1111/j.1538-7836.2004.01019.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of denaturing high‐performance liquid chromatography (DHPLC) in the screening of mutations in hemophilia B patients

Abstract: D in other cell types, e.g. keratinocytes [6] and osteoblasts [7]. Elevated PAI-1 levels have been implicated as a risk factor for cardiovascular events including myocardial infarction and stroke [8]. Patients with ESRD are known to have impaired fibrinolysis [9], in part, due to increased circulating levels of active PAI-1 [10].In summary, the expression of PAI-1, but not other gene products, was markedly reduced in paricalcitol vs. calcitrioltreated cells at concentrations of paricalcitol (4 nM) that are obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…The mutational detection rate was 34.1 and 51.3% for the probands and the relatives, respectively, which is comparable to what has been found in other studies (22,(31)(32)(33)(34). Even though the mutational detection rate is high when using DHPLC with sensitivity above 95% (35), this study did not confirm mutations in all probands. This might in part be due to the inclusion criteria, as Jensen et al (16) reported a 80% mutation detection rate when using strict inclusion criteria's with a P-Chl of 10.6 mmol/l and the presence of extra-vascular lipid deposits in more than 85.6% of the patients.…”
Section: Discussionsupporting
confidence: 82%
“…The mutational detection rate was 34.1 and 51.3% for the probands and the relatives, respectively, which is comparable to what has been found in other studies (22,(31)(32)(33)(34). Even though the mutational detection rate is high when using DHPLC with sensitivity above 95% (35), this study did not confirm mutations in all probands. This might in part be due to the inclusion criteria, as Jensen et al (16) reported a 80% mutation detection rate when using strict inclusion criteria's with a P-Chl of 10.6 mmol/l and the presence of extra-vascular lipid deposits in more than 85.6% of the patients.…”
Section: Discussionsupporting
confidence: 82%
“…It is possible that the sensitivity for mutation detection wase xceededf or exon b+cP CR (513bp) as the optimalfragment size for mutation detection by CSGE is between 200-450bp(2). This sensitivity is comparable to thatr eported ford enaturing gradient gel electrophoresis (90.9%), single strand conformation polymorphisma nalysis (90.4%)but less than the 100% reported for denaturing high performancel iquid chromatography, at echnique thati sn ot commonlyavailable (6)(7)(8).…”
supporting
confidence: 53%
“…In contrast, the large size and complexity of the F8 gene necessitates amplifications of genomic DNA in over 30 fragments to cover the target regions. 19 Various mutation screening techniques can be used to screen PCR products of F8 or F9 genes, such as single-strand conformation polymorphism, 20 denaturing gradient gel electrophoresis, 21 conformationsensitive gel electrophoresis (CSGE), 19 and denaturing high pressure liquid chromatography 22 with sensitivities ranging from 80 to 98%. Abnormal PCR product profiles are sequenced to identify the nucleotide change.…”
Section: Direct Mutation Detectionmentioning
confidence: 99%